Hydrogen production from methanol partial oxidation through the catalyst prepared using torrefaction liquid products. (1st November 2020) - Chih, Yi-Kai; Chen, Wei-Hsin; Tran, Khanh-Quang
Graphical abstract: Highlights: Torrefied liquid products (TLPs) typically exhibit low pH values between 2 and 3. For the first time, TLPs are used as acid catalysts in the sol-gel process for TEOS. Methanol conversion over 92% could be achieved for most of the prepared catalysts. H2 yield could reach up to 1.35 mol/(mol methanol) from the prepared catalysts. TLPs Application for catalysts can simultaneously fulfill hydrogen economy and bioeconomy. Abstract: This study developed a novel application of torrefaction liquid products (TLPs) for acidic catalyst sol-gel synthesis of SiO2 from tetraethyl orthosilicate (TEOS) to improve the thermal stability of Al2 O3 catalyst supporter. The Al2 O3 supporter coated with SiO2 was used to prepare six Pt catalysts for fulfilling hydrogen production from methanol partial oxidation in sprays. A commercial h-BN Pt/Al2 O3 catalyst was also adopted for comparison. The results suggested that the methanol conversion over 92% could be achieved for most of the prepared Pt/SiO2 @Al2 O3 catalysts, while the H2 yield could reach up to 1.35 mol/(mol methanol) which was higher than that of the commercial h-BN Pt/Al2 O3 catalyst. Accordingly, TLPs can be suitably employed as acid catalysts for SiO2 sol-gel synthesis for preparing Pt/SiO2 @Al2 O3 catalysts to effectively convert methanol to hydrogen. This novel application can simultaneously fulfill the hydrogen economy and bioeconomy in the industry while producing biochar through biomass torrefaction.